Time-varying uncertainty and the credit channel - Viktor Dorofeenko; Gabriel S. Lee; Kevin D. Salyer (Institute for Advanced Studies (IHS), 2002)
We extend the Carlstrom and Fuerst (1997) agency cost model of business cycles by including time varying uncertainty in the technology shocks that affect capital production. We first demonstrate that standard linearization methods can be used to solve the model yet second moment effects still influence equilibrium characteristics. The effects of the persistence of uncertainty are then analyzed. Our primary findings fall into three broad categories. First, it is demonstrated that uncertainty affects the level of the steady-state of the economy so that welfare analyses of uncertainty that focus entirely on the variability of output (consumption) will understate the true costs of uncertainty. A second key result is that time varying uncertainty results in countercyclical bankruptcy rates - a finding which is consistent with the data and opposite the result in Carlstrom and Fuerst. Third, we show that persistence of uncertainty affects both quantitatively and qualitatively the behavior of the economy.
Keywords: E2; E4; E5; 330; agency costs; credit channel; time-varying uncertainty; Konjunktur; Konjunkturtheorie; Prinzipal-Agent-Theorie; Risiko